A two-dimensional material / polymer / porous membrane composite membrane and a preparation method and application thereof
Patent Information
- Application Number
- CN202410234187.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-29
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-02-29
AI Technical Summary
When preparing Nafion/graphene composite membranes using existing hot-pressing methods, the graphene films are easily broken and the bonding is not strong, making it difficult to maintain stability in a liquid environment, resulting in poor separation performance.
The proton exchange polymer solution hydration method is adopted. By transferring the proton exchange polymer in a water vapor environment, a stable solid-solid interface is formed between the two-dimensional material membrane and the porous membrane. This avoids the damage caused by hot pressing and ensures that the graphene is transferred completely and bonded to the porous membrane.
The prepared composite membrane has a stable structure and can maintain good hydrogen-deuterium separation performance for a long time, preventing swelling and curling, and is suitable for maintaining stability in liquid environments.
Smart Images

Figure CN117942777B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrogen-deuterium separation composite membrane technology, specifically to a two-dimensional material / polymer / porous membrane composite membrane, its preparation method, and its application. Background Technology
[0002] Graphene is a two-dimensional material composed of carbon atoms with many unique physical and chemical properties. Researchers have recently discovered its great potential in isolating hydrogen isotopes. Hydrogen isotopes are hydrogen atoms with the same atomic number but different mass numbers. In nature, hydrogen is found primarily in the form of protium (…). 1 H), deuterium ( 2 H), tritium ( 3 The graphene membrane exists in three isotopic forms (H, G, and T). Specifically, hydrogen and deuterium can be separated using an electrochemical pump.
[0003] Currently, the conventional method for preparing Nafion / graphene composite membranes for hydrogen-deuterium separation is the hot-pressing method. This method involves directly hot-pressing a solid-solid Nafion membrane onto a substrate such as a copper foil with graphene grown on it at approximately 140°C under pressure at the solid-solid interface. The membrane is then immersed in an etching solution to etch away the copper foil substrate, leaving a clean Nafion / graphene composite membrane. The solid Nafion membrane has a smooth surface, softens at high temperatures, and exhibits increased adhesion. Under certain pressure, it can bond firmly with graphene, thus facilitating the transfer of the graphene.
[0004] Existing hot-pressing methods require appropriate pressure, and the transfer results are greatly affected by the flatness of the graphene substrate. Furthermore, the Nafion film and graphene form a solid-solid interface in the hot-pressing process; the pressure applied during the process may cause uneven areas of the graphene to break upon bonding with the Nafion film, thus damaging the integrity of the graphene film. In addition, the unavoidable presence of gaps at the solid-solid interface makes it difficult for the Nafion film and graphene to bond firmly, leading to material detachment in liquid environments. Therefore, finding a new method to prepare proton exchange polymer / two-dimensional material composite films to avoid these problems is a pressing technical challenge. Summary of the Invention
[0005] Therefore, the present invention provides a composite membrane of two-dimensional material / polymer / porous membrane, its preparation method and application, so as to prepare a structurally stable composite membrane of two-dimensional material / polymer / porous membrane.
[0006] In a first aspect, the present invention provides a composite membrane of a two-dimensional material / polymer / porous membrane, the composite membrane comprising a two-dimensional material membrane, a proton exchange polymer membrane, and a porous membrane; wherein the proton exchange polymer membrane is located between the two-dimensional material membrane and the porous membrane, and the porous membrane optionally contains a proton exchange polymer.
[0007] Secondly, the present invention provides a method for preparing the composite membrane of the two-dimensional material / polymer / porous membrane, the preparation method comprising the following steps:
[0008] (1) Provide a filled porous membrane filled with a proton exchange polymer;
[0009] (2) The filled porous membrane is covered on a two-dimensional material membrane supported on a substrate and then placed in a water vapor environment so that at least a portion of the proton exchange polymer filled in the porous membrane is transferred between the porous membrane and the two-dimensional material membrane, and optionally a portion of the proton exchange polymer is retained in the porous membrane.
[0010] (3) Remove the substrate and then dry it to obtain the composite membrane of the two-dimensional material / polymer / porous membrane.
[0011] Thirdly, the present invention also provides an application of a two-dimensional material / polymer / porous membrane composite membrane in hydrogen-deuterium separation, wherein the two-dimensional material / polymer / porous membrane composite membrane is selected from the two-dimensional material / polymer / porous membrane composite membrane described in the first aspect, or is prepared by the method described in the second aspect.
[0012] Beneficial effects:
[0013] In the preparation of the composite membrane of two-dimensional material / polymer / porous membrane by this invention, the interface between the proton exchange polymer and the two-dimensional material membrane is transformed from a solid-liquid interface to a solid-solid interface. The two-dimensional material membrane is completely transferred into the composite membrane, and the connection between the proton exchange polymer membrane and the two-dimensional material membrane is more stable and has good stability. When the composite membrane is used for hydrogen-deuterium separation, it can maintain good separation performance for a long time. The porous membrane is retained in the composite membrane, which effectively prevents swelling and curling. The composite membrane can remain stable and not easily deformed in a liquid environment. Attached Figure Description
[0014] Figure 1 These are the Raman spectra of the composite films prepared in Example 1 and Comparative Example 2, where Nafion / Graphene is the spectral line of the graphene / Nafion / PES composite film prepared in Example 1, and Nafion is the spectral line of the Nafion / PES composite film prepared in Comparative Example 2.
[0015] Figures 2-4 These are scanning electron microscope (SEM) images of the composite membrane prepared in Example 1;
[0016] Figure 5 This is a schematic diagram of the structure of the composite membrane prepared in Example 1;
[0017] Figure 6 and Figure 7 These are schematic diagrams of the intermediate devices obtained in steps (2) and (4) of Example 1, respectively.
[0018] Figure 8 and Figure 9 These are scanning electron microscope (SEM) images of the graphene / Nafion composite film prepared in Comparative Example 1 and the graphene / Nafion / PES composite film prepared in Example 1 after 41 hours of continuous operation. Detailed Implementation
[0019] The present application will now be described in further detail with reference to the accompanying drawings and embodiments. Through these descriptions, the features and advantages of the present application will become clearer and more apparent.
[0020] The term “exemplary” as used herein means “serving as an example, embodiment, or illustration.” Any embodiment illustrated herein as “exemplary” is not necessarily to be construed as superior to or better than other embodiments. Although various aspects of embodiments are shown in the accompanying drawings, the drawings are not necessarily drawn to scale unless specifically indicated otherwise.
[0021] Furthermore, the technical features involved in the different embodiments of this application described below can be combined with each other as long as they do not conflict with each other.
[0022] In a first aspect, the present invention provides a composite membrane of a two-dimensional material / polymer / porous membrane, the composite membrane comprising a two-dimensional material membrane, a proton exchange polymer membrane, and a porous membrane; wherein the proton exchange polymer membrane is located between the two-dimensional material membrane and the porous membrane, and the porous membrane optionally contains a proton exchange polymer.
[0023] It should be noted that the optional inclusion of a proton exchange polymer in the porous membrane indicates that the porous membrane may or may not contain a proton exchange polymer. When the porous membrane contains a proton exchange polymer, the proton exchange polymer exists in the composite membrane in two parts: one part of the proton exchange polymer is distributed between the two-dimensional material membrane and the porous membrane in the form of a proton exchange polymer membrane, and the other part of the proton exchange polymer can fill the pores of the porous membrane in the form of polymer particles.
[0024] In one embodiment of the composite film of the present invention, the thickness of the two-dimensional material film is 0.3 to 1 nm.
[0025] In one embodiment of the composite membrane described above, the thickness of the proton exchange polymer membrane is 20–40 μm.
[0026] In one embodiment of the composite membrane described above, the thickness of the porous membrane is 100–120 μm.
[0027] In one embodiment of the composite membrane of the present invention, the proton exchange polymer accounts for 20% to 40% of the mass of the porous membrane.
[0028] It should be noted that, in the composite membrane of the present invention, by controlling the thickness of the two-dimensional material membrane, the thickness of the proton exchange polymer membrane, the thickness of the porous membrane, and the mass ratio of the proton exchange polymer in the porous membrane as described above, the composite membrane structure can be made more stable and the two-dimensional material transfer effect can be better.
[0029] In another embodiment of the composite membrane described above, the proton exchange polymer in the proton exchange polymer membrane is the same as the proton exchange polymer in the porous membrane, and is selected from one or more of Nafion, PMMA, and PPC; and / or, the two-dimensional material membrane is selected from graphene membrane, graphene derivative membrane, transition metal sulfide membrane, transition metal boride membrane, black phosphorus membrane, or topological insulator membrane.
[0030] Nafion, short for perfluorosulfonic acid polymer, is a polymer with ionic properties and excellent selectivity for cations. Based on this characteristic, Nafion is often used as a proton exchange membrane. Proton exchange polymers are not limited to Nafion; carbon-chain polymers, heterochain polymers, and organometallic polymers with cation selectivity are also applicable and fall within the scope of this invention. The two-dimensional material membrane refers to a two-dimensional layered material membrane, which can be selected from two-dimensional membrane layers with hydrogen isotope separation properties.
[0031] In one embodiment of the composite membrane described above in this invention, the porosity of the porous membrane is 10% to 50%; the porous membrane is selected from PES porous membrane, PC porous membrane, PET porous membrane or PI porous membrane.
[0032] It should be noted that the porous membranes applicable to this invention are not limited to the types mentioned above. Other porous media membranes that meet the above porosity requirements are also applicable and fall within the scope of this invention. As a preferred embodiment, the size of the porous membrane is larger than that of the two-dimensional material membrane (and also larger than the substrate supporting the two-dimensional material membrane). This allows the two-dimensional material membrane to be completely supported by the proton exchange polymer membrane and the porous membrane, and the two-dimensional material membrane can be completely transferred during the preparation of the composite membrane.
[0033] Secondly, the present invention provides a method for preparing the above-mentioned two-dimensional material / polymer / porous membrane composite membrane, the preparation method comprising the following steps:
[0034] (1) Provide a filled porous membrane filled with a proton exchange polymer;
[0035] (2) The filled porous membrane is covered on a two-dimensional material membrane supported on a substrate and then placed in a water vapor environment so that at least a portion of the proton exchange polymer filled in the porous membrane is transferred between the porous membrane and the two-dimensional material membrane, and optionally a portion of the proton exchange polymer is retained in the porous membrane.
[0036] (3) Remove the substrate and then dry it to obtain the composite membrane of the two-dimensional material / polymer / porous membrane.
[0037] It should be noted that in step (1), after filling, the proton exchange polymer can be filled into the pores of the porous membrane in the form of a solution. After step (2) and standing in a water vapor environment, the water vapor causes at least a portion of the proton exchange polymer filled in the porous membrane to transfer between the porous membrane and the two-dimensional material membrane. A solid-liquid interface is formed between the proton exchange polymer and the two-dimensional material membrane. After drying in the subsequent step (3), the solid-liquid interface between the proton exchange polymer and the two-dimensional material membrane is transformed into a solid-solid interface. That is, the proton exchange polymer between the porous membrane and the two-dimensional material membrane is dried and dehydrated to form a proton exchange polymer membrane, and finally a composite membrane of two-dimensional material / polymer / porous membrane is obtained.
[0038] In step (2), the option to retain a portion of the proton exchange polymer in the porous membrane means that: a portion of the proton exchange polymer may be retained in the porous membrane, or no proton exchange polymer may be retained in the porous membrane, that is, all the proton exchange polymer is transferred to the space between the porous membrane and the two-dimensional material membrane to form a proton exchange polymer membrane.
[0039] Through years of research and experimentation, the inventors of this application have discovered that the composite membrane prepared by the hydration method of the proton exchange polymer solution of this invention for two-dimensional materials / polymers / porous membranes has several advantages. First, it avoids the problems of material damage and weak bonding caused by hot-pressing of the solid-solid interface between graphene and polymer in the hot-pressing method. The solid-solid interface between the proton exchange polymer membrane and the two-dimensional material membrane is transformed from the solid-liquid interface. Therefore, the interfacial connection between the two-dimensional material membrane and the proton exchange polymer membrane is more stable and firm, and the structure of the resulting composite membrane is more stable.
[0040] Secondly, the proton exchange polymer transferred from the pores of the porous membrane comes into full contact with the two-dimensional material membrane in solution form, and then transforms into a solid-solid interface between the proton exchange polymer membrane and the two-dimensional material membrane, thus ensuring the integrity of the transfer of the two-dimensional material membrane.
[0041] Third, the composite membrane finally prepared by the above method of the present invention retains a porous membrane. The porous membrane has ion permeability and can provide effective support for the proton exchange polymer membrane to prevent swelling, curling, etc. The composite membrane of two-dimensional material / polymer / porous membrane can remain stable and not easily deformed in the liquid environment.
[0042] In addition, some proton exchange polymers can be retained in the porous membrane. These proton exchange polymers are connected to the proton exchange polymer membrane formed by the proton exchange polymers between the porous membrane and the two-dimensional material membrane, and together they combine with the porous membrane to make the structure more compact. Therefore, the composite membrane has better stability and can maintain good separation performance for a long time when used for hydrogen-deuterium separation.
[0043] In one embodiment of the above method of the present invention, in step (1), the filled porous membrane is obtained by immersing the porous membrane in a solution of a proton exchange polymer; the mass concentration of the proton exchange polymer solution is 3% to 15%; the porous membrane is a circle with a diameter of 20 to 30 mm; and the immersion time is 5 to 20 min.
[0044] It should be noted that the preparation method of this invention uses a porous membrane as the substrate layer, employs a proton exchange polymer solution hydration method, and transfers a two-dimensional material membrane to form a composite membrane of two-dimensional material / polymer / porous membrane. By controlling the mass concentration and wetting time of the proton exchange polymer solution, the amount or loading of proton exchange polymer in the porous membrane is sufficient to ensure that the proton exchange polymer in the porous membrane can form a good proton exchange polymer membrane between the porous membrane and the two-dimensional material membrane after subsequent settling and drying in a water vapor environment.
[0045] In another embodiment of the method described above, the preparation method further includes the following steps between steps (1) and (2):
[0046] A substrate carrying a two-dimensional material film is placed on the first back plate;
[0047] When the substrate has a two-dimensional material film on only one side, the substrate is bonded to the first backplate.
[0048] It should be noted that when the substrate has two-dimensional material films on both sides, either side of the two-dimensional material film can be attached to the first back plate when it is placed on the first back plate. When the substrate has only one side of the two-dimensional material film, the substrate is attached to the first back plate, and the two-dimensional material film on the substrate is exposed upwards to facilitate subsequent steps.
[0049] In one embodiment of the method described above, step (2) further includes the following step before placing the object in a water vapor environment:
[0050] A rigid sheet is placed on the filled porous membrane, and then the filled porous membrane and the first back plate are fixed; and / or, the time of placement in the water vapor environment is 15 to 40 minutes.
[0051] It should be noted that before hydration in a water vapor environment, a rigid sheet is attached to the filled porous membrane. The rigid sheet applies a flat pressure downward to the porous membrane, so that the proton exchange polymer between the porous membrane and the two-dimensional material membrane can form an atomically flat proton exchange polymer interface (i.e., a proton exchange polymer membrane) between the porous membrane and the two-dimensional material membrane.
[0052] The rigid sheet can be made of a flat, rigid material such as mica, silicon, or glass. The size of the rigid sheet is not smaller than that of the two-dimensional material membrane (nor smaller than the substrate carrying the two-dimensional material membrane). The filled porous membrane and the first backing plate can be fixed with adhesive tape to ensure that the porous membrane is fixed and will not slip during subsequent hydration in a water-vapor environment.
[0053] By controlling the time spent in a water vapor environment as described above, some or all of the proton exchange polymer filled in the porous membrane is transferred to the space between the porous membrane and the two-dimensional material membrane to form a proton exchange polymer membrane (liquid membrane), while the remaining proton exchange polymer remains in the porous membrane. Alternatively, all of the proton exchange polymer filled in the porous membrane is transferred to the space between the porous membrane and the two-dimensional material membrane to form a proton exchange polymer membrane.
[0054] In one embodiment of the method described above, the preparation method further includes the following steps between steps (2) and (3):
[0055] Remove the rigid sheet, and transfer the substrate, the two-dimensional material membrane, the porous membrane, the proton exchange polymer between the two-dimensional material membrane, and the porous membrane retaining an optional portion of the proton exchange polymer together to the second back plate, with the porous membrane retaining an optional portion of the proton exchange polymer attached to the second back plate;
[0056] The substrate is fixed and a porous membrane containing an optional portion of the proton exchange polymer is retained. The second backplate is fixed and a porous membrane containing an optional portion of the proton exchange polymer is retained.
[0057] It should be noted that during the transfer to the second backplate, the positional relationship of each membrane layer remains unchanged, i.e., the positional relationship of substrate / two-dimensional material membrane / proton exchange polymer / porous membrane is maintained. The substrate / two-dimensional material membrane / proton exchange polymer / porous membrane is placed on the second backplate with the porous membrane in direct contact with the second backplate, with the substrate on top. Taking a copper foil as an example, if one side of the copper foil carries the two-dimensional material membrane, then the copper foil is on top and exposed. If both sides of the copper foil carry the two-dimensional material membrane, then the two-dimensional material membrane carried on the other side of the copper foil is on top and exposed. Transferring the membrane to the second backplate in this manner facilitates subsequent steps to remove the substrate and obtain the composite membrane.
[0058] The substrate and the porous membrane retaining an optional portion of the proton exchange polymer can be fixed by tape, or the second backplate and the porous membrane retaining an optional portion of the proton exchange polymer can be fixed by tape. Fixing with tape can ensure the stability of each structure during subsequent wet etching.
[0059] It should be noted that the first and second back plates serve to fix and support the structure. The thickness of the first and second back plates can be around 0.25mm. PET, PVC, PC, PTFE, etc. can be used as the first or second back plates.
[0060] In one embodiment of the above method of the present invention, the substrate is selected from a metal substrate or a silicon dioxide substrate, and the metal substrate is selected from a copper substrate or a nickel substrate; the substrate is a copper substrate and only one side is covered with the two-dimensional material film, and step (3) removes the substrate by wet etching; or, the substrate is a copper substrate and both sides are covered with two-dimensional material films, and step (3) removes the substrate by sequentially performing dry etching and wet etching.
[0061] It should be noted that when the substrate is a copper substrate and only one side carries the two-dimensional material film, the copper substrate, such as a copper foil, can be removed by wet etching with ammonium sulfate solution. The substrate / two-dimensional material film / proton exchange polymer / porous membrane is then transformed into a two-dimensional material film / proton exchange polymer / porous membrane, which is then dried to obtain a two-dimensional material film / proton exchange polymer film / porous membrane.
[0062] When the substrate is a copper substrate and two-dimensional material films are respectively carried on both sides, in addition to the two-dimensional material film on one side, there is also a two-dimensional material film on the other side. The device structure to be performed in step (3) can be represented as two-dimensional material film / substrate / two-dimensional material film / proton exchange polymer / porous film. First, the two-dimensional material film on the other side of the substrate is removed by dry etching to obtain substrate / two-dimensional material film / proton exchange polymer / porous film. Then, the substrate is removed by wet etching to obtain two-dimensional material film / proton exchange polymer / porous film. Then, the two-dimensional material film / proton exchange polymer film / porous film is obtained by subsequent drying steps.
[0063] The substrate carrying the two-dimensional material film used in this invention can be purchased as a finished product or prepared by methods such as CVD.
[0064] Thirdly, the present invention also provides an application of a composite membrane of two-dimensional material / polymer / porous membrane in hydrogen-deuterium separation, wherein the composite membrane of two-dimensional material / polymer / porous membrane is the composite membrane of two-dimensional material / polymer / porous membrane described in the first aspect above, or is prepared by the preparation method of the second aspect above.
[0065] In this invention, perfluorosulfonic acid resin is abbreviated as Nafion, polymethyl methacrylate is abbreviated as PMMA, polymethyl ethylene carbonate is abbreviated as PPC, polyethersulfone is abbreviated as PES, polycarbonate is abbreviated as PC, polyethylene terephthalate is abbreviated as PET, polyimide is abbreviated as PI, graphene is abbreviated as Gr, and mica is abbreviated as mica.
[0066] The present invention will be further described in detail below through examples, but these examples are not intended to limit the invention. In the following examples, unless otherwise specified, the experimental instruments and raw materials involved are all commercially available products.
[0067] The following examples use:
[0068] The PES porous membrane was purchased from the Taobao store Alpha Experimental Mall. The PES porous membrane is a circle with a diameter of 25mm, a thickness of 110μm, and a porosity of 50%.
[0069] Liquid Nafion was purchased from Shanghai Titan Technology Co., Ltd., with a mass concentration of 5%.
[0070] The PET backing was purchased from the Taobao store Renyuan Flagship Store, and its thickness is 0.3mm.
[0071] The copper foil was purchased from Alfa Aesar, with a thickness of 25 μm and a purity of 99.8%.
[0072] The mica sheet was purchased from Nanjing Muke Nanotechnology Co., Ltd., with a length of 25mm, a width of 20mm, a thickness of 0.15mm, and a purity of 99.995%.
[0073] Example of preparation of graphene-grown copper foil
[0074] (1) Cut copper foil with a length of 9cm and a width of 1.5cm, treat the surface with 3% ammonium persulfate solution for 3min, then wash the surface with deionized water to remove the residual ammonium persulfate solution for 5min, and finally wash with anhydrous ethanol for 1min. Use N2 to blow dry the anhydrous ethanol on the surface of the copper foil.
[0075] (2) The processed copper foil is placed in a tube furnace for CVD growth. Under low pressure and 1030°C, H2 is introduced at a flow rate of 50 sccm. The copper foil is annealed for 30 min in a hydrogen atmosphere. Then the flow rate of H2 is changed to 10 sccm, CH4 is introduced at a flow rate of 7 sccm, and the growth is carried out for 20 min. Heating is stopped, and the cooling is completed within 1 h to obtain a copper foil that is completely covered by a single layer of graphene on both sides.
[0076] Example 1
[0077] Preparation method steps:
[0078] (1) Immerse the PES porous membrane in liquid Nafion (5wt%) for 10 min to allow the liquid Nafion to fill the pores of the PES porous membrane;
[0079] (2) Place a copper foil with graphene grown on a PET backplate (prepared according to the above-described example of graphene grown copper foil preparation), with one side of the graphene facing upwards. Cover the graphene on the copper foil with a fully impregnated PES porous membrane, and then cover the PES porous membrane with a mica sheet, ensuring a tight fit between the PES porous membrane and the graphene on the copper foil. Secure the PES porous membrane and the PET backplate around the perimeter with adhesive tape. A schematic diagram of the intermediate device obtained in this step is shown below. Figure 6 As shown (graphene on the other side of the copper foil is omitted and not shown);
[0080] (3) Place the above samples in a water vapor environment at 120℃ and let them stand for 20 minutes to hydrate;
[0081] The specific water vapor environment is as follows:
[0082] Place the device to be hydrated and a small glass dish containing deionized water on a 120℃ heating plate. Invert the large glass dish on the heating plate, with the device to be hydrated and the small glass dish below the large glass dish, so that the device environment on the heating plate is filled with water vapor.
[0083] (4) Remove the mica sheet, the tape used for fixing, and the PET backing. Transfer the bonded copper foil, graphene, and PES porous membrane to a new clean PET backing with the copper foil side facing up (i.e., the graphene side facing up on the other side). The PES porous membrane is in contact with the clean PET backing and fixed around the edges with tape. Specifically, fix the copper foil and PES porous membrane, the PES porous membrane, and the clean PET backing at the bottom.
[0084] Because the preparation example of growing graphene copper foil yields Gr / Cu / Gr, this step produces PET-PES-Nafion-Gr-Cu-Gr; the structural schematic diagram of the intermediate device obtained in this step is shown below. Figure 7As shown (the graphene on the other side of the Nafion film and copper foil is omitted in the diagram);
[0085] (5) Dry etching of the PET-PES-Nafion-Gr-Cu-Gr obtained in step (4) under the following conditions: 80 sccm O2, 20 sccm Ar atmosphere, 50W power RF for 100s; the graphene on the other side of the copper foil is removed by dry etching.
[0086] The device after dry etching was subjected to wet etching. The device was placed upside down in a 0.5 mol / L ammonium persulfate solution. After 90 min, the copper foil was completely etched. The etched device was then soaked in deionized water for 30 min to remove the ammonium persulfate from the device surface. The PET backplate was then removed to obtain the device.
[0087] (6) After drying the device at room temperature, a graphene / Nafion / PES composite film is finally obtained. The structure of the composite film can be as follows: Figure 5 As shown.
[0088] Comparative Example 1: Graphene / Nafion composite film prepared by hot pressing method
[0089] The copper foil (referred to as Gr / Cu / Gr) with graphene grown on both sides prepared in the above preparation example and the Nafion film with a thickness of 18 μm (purchased from Gore, item number M73518) were placed on a hot press (purchased from Hefei Kejing Materials Technology Co., Ltd.). The temperature of the upper and lower plates of the hot press was set to 140℃, the pressure was set to 300 kg, and the holding time was 5 min. The Gr / Cu / Gr and the Nafion film were hot-pressed together. Then, the copper foil was removed by dry etching and wet etching in step (5) of the above example to obtain the graphene / Nafion composite film.
[0090] Comparative Example 2
[0091] The Nafion / PES composite membrane was prepared according to the method of Example 1, but the difference from Example 1 is as follows:
[0092] The copper foil used is the initial state of copper foil without graphene growth. In step (5), wet etching is performed directly without dry etching to obtain the Nafion / PES composite film.
[0093] Test Example 1
[0094] Raman spectroscopy analysis was performed on the graphene / Nafion / PES composite film prepared in Example 1 and the Nafion / PES composite film prepared in Comparative Example 2. The obtained Raman spectra are shown below. Figure 1 As shown. By Figure 1 The results showed that, compared to the Nafion / PES composite membrane ( Figure 1The spectral lines of Nafion (identified in Chinese), and the composite film prepared in Example 1 ( Figure 1 The Chinese character Nafion / Graphene is located at 2690cm. -1 The presence of a distinct graphene 2D peak indicates that graphene was successfully transferred onto the Nafion film.
[0095] In addition, the copper foil on which graphene was grown was characterized by in-situ Raman spectroscopy, which showed that the graphene film in the composite film prepared in Example 1 was a single atomic layer with a thickness of 0.34 nm.
[0096] Measurements taken with vernier calipers revealed that the composite membrane prepared in Example 1 contained:
[0097] The thickness of the PES porous membrane is 110 μm; the thickness of the Nafion membrane (proton exchange polymer membrane) between the graphene membrane and the PES porous membrane is 30 μm.
[0098] Weighing with an electronic balance revealed that the composite membrane prepared in Example 1 contained:
[0099] The mass percentage of Nafion (proton exchange polymer) in the PES porous membrane is 33%.
[0100] Test Example 2
[0101] The graphene / Nafion / PES composite film prepared in Example 1 was analyzed by scanning electron microscopy (SEM), and the obtained SEM images are shown below. Figures 2-4 As shown. In Figures 2-4 In the diagram, from top to bottom, the membrane layers are a graphene (Gr) membrane, a Nafion membrane, and a PES porous membrane. A schematic diagram of the graphene / Nafion / PES composite membrane prepared in Example 1 is shown below. Figure 5 As shown. In Figure 3 and Figure 4 In the image, the pores of the PES porous membrane (black pore areas) are visible, with only a small area of bare pores exposed in the bright region, showing no Nafion filling or graphene transfer. Furthermore, optical microscopy (OM) characterization reveals a continuous graphene film on the surface of the composite membrane, combined with... Figures 2-4 As can be seen, the graphene on the surface of the composite film device prepared in Example 1 is intact without obvious defects, and the graphene coverage is as high as 99% or more. The integrity of the graphene in the composite film results in a more stable connection between the graphene film and the Nafion film.
[0102] Test Example 3
[0103] The composite membrane prepared in Example 1 was used as a hydrogen-deuterium separation membrane in an electrochemical pump for electrolysis testing. Platinum electrodes suitable for water electrolysis were used as the cathode and anode. A 20% heavy water stock solution was prepared based on 99.9% heavy water (E090001) from Anengji Chemical. The electrolysis was conducted at 0.5 A / cm². 2 At a current density of 1, 6 mL of 20% heavy water stock solution was added, and after electrolysis for 23 h, 1 mL of 49% heavy water was obtained, with a hydrogen-to-deuterium separation ratio of 5.8.
[0104] The concentration of heavy water stock solution or heavy water obtained by electrolysis was detected by nuclear magnetic resonance.
[0105] Hydrogen-deuterium separation ratio = Hydrogen ions consumed in electrolysis ÷ Deuterium ions consumed in electrolysis
[0106] Additionally, using the same method, at 0.8 A / cm 2 At the specified current density, the composite membrane, when used as a separation membrane, maintained a separation ratio of 4.2 for 41 hours, indicating that the composite membrane has good separation stability and can maintain good hydrogen-deuterium separation performance for a long time.
[0107] Using the same method and testing conditions, the composite membrane prepared by the hot-pressing method in Comparative Example 1 was tested at 0.5 A / cm. 2 At a current density of 0.8 A / cm², after 23 hours of electrolysis, the hydrogen-to-deuterium separation ratio was 4.8. 2 At the specified current density, the composite membrane, when used as a separation membrane, can maintain a separation ratio of 3.9 for 41 hours of continuous operation.
[0108] The graphene / Nafion composite film prepared in Comparative Example 1 was analyzed by scanning electron microscopy (SEM) after 41 hours of continuous operation. The obtained SEM images are shown below. Figure 8 As shown, the composite film exhibits obvious tearing and curling. The graphene / Nafion / PES composite film prepared in Example 1 was analyzed by scanning electron microscopy (SEM) after 41 hours of continuous operation. The obtained SEM images are shown below. Figure 9 As shown, the composite membrane still maintains good integrity.
[0109] Test Example 4
[0110] The swelling ratio of the membrane is calculated by weighing. The specific test method is as follows:
[0111] Weigh the dry membrane of the composite membrane prepared in Example 1 before swelling, and then soak the membrane in water for 24 hours (preliminary experiments show that the mass of the wet membrane basically does not change after soaking for 24 hours, at which point it can be considered to have fully swollen). After taking out the membrane, quickly wipe off the surface moisture with filter paper and weigh it. The difference between the mass of the dry membrane and the wet membrane is the maximum amount of solvent that the membrane can adsorb.
[0112] The swelling ratio is the ratio of the amount of solvent adsorbed by the membrane to the mass of the dry membrane. Through testing and calculation, the swelling ratio of the composite membrane prepared in Example 1 was 8.97%, while the swelling ratio of the Adamas (catalog number 011265339) Nafion membrane was 10.53%, indicating that porous membranes can provide effective support for proton exchange polymer membranes, reducing the swelling ratio.
[0113] The present application has been described above with reference to preferred embodiments; however, these embodiments are merely exemplary and illustrative. Various substitutions and modifications can be made to the present application based on these embodiments, all of which fall within the protection scope of the present application.
Claims
1. A method for preparing a composite membrane of a two-dimensional material / polymer / porous membrane, characterized in that, The preparation method includes the following steps: (1) A filled porous membrane filled with a proton exchange polymer is provided; the filled porous membrane is obtained by impregnating a porous membrane in a solution of the proton exchange polymer; (2) The filled porous membrane is covered on a two-dimensional material membrane supported on a substrate, and then placed in a water vapor environment so that at least a portion of the proton exchange polymer filled in the porous membrane is transferred between the porous membrane and the two-dimensional material membrane, a portion of the proton exchange polymer is retained in the porous membrane, and a solid-liquid interface is formed between the proton exchange polymer between the porous membrane and the two-dimensional material membrane and the two-dimensional material membrane. (3) Remove the substrate and then dry it to transform the solid-liquid interface into a solid-solid interface to obtain the composite membrane of the two-dimensional material / polymer / porous membrane. The composite membrane comprises a two-dimensional material membrane, a proton exchange polymer membrane, and a porous membrane; wherein the proton exchange polymer membrane is located between the two-dimensional material membrane and the porous membrane, and the porous membrane contains a proton exchange polymer; the mass percentage of the proton exchange polymer in the porous membrane is 20% to 40%. The proton exchange polymer in the proton exchange polymer membrane is the same as the proton exchange polymer in the porous membrane, and is selected from Nafion; The two-dimensional material film is a two-dimensional layered material film, and the two-dimensional material film is selected from graphene film, graphene derivative film, and transition metal sulfide film.
2. The preparation method according to claim 1, characterized in that, The thickness of the two-dimensional material film is 0.3~1 nm; The thickness of the proton exchange polymer membrane is 20~40 μm; The thickness of the porous membrane is 100~120 μm.
3. The preparation method according to claim 2, characterized in that, The porosity of the porous membrane is 10%~50%; The porous membrane is selected from PES porous membrane or PC porous membrane.
4. The preparation method according to claim 1, characterized in that, The mass concentration of the proton exchange polymer solution is 3% to 15%; The porous membrane is a circle with a diameter of 20-30 mm, and the immersion time is 5-20 min.
5. The preparation method according to claim 1, characterized in that, The preparation method further includes the following steps between steps (1) and (2): A substrate carrying a two-dimensional material film is placed on the first back plate; When the substrate has a two-dimensional material film on only one side, the substrate is bonded to the first backplate.
6. The preparation method according to claim 5, characterized in that, Step (2) includes the following steps before placing the object in a water vapor environment: A rigid sheet is placed on the filled porous membrane, and then the filled porous membrane and the first backing plate are fixed; and / or, The time spent in the water vapor environment is 15-40 minutes.
7. The preparation method according to claim 6, characterized in that, The preparation method further includes the following steps between steps (2) and (3): Remove the rigid sheet, and transfer the substrate, the two-dimensional material membrane, the porous membrane, the proton exchange polymer between the two-dimensional material membrane, and the porous membrane with a portion of the proton exchange polymer retained together to the second back plate, with the porous membrane with a portion of the proton exchange polymer retained attached to the second back plate; The substrate and a porous membrane retaining a portion of the proton exchange polymer are fixed together, and the second backplate and a porous membrane retaining a portion of the proton exchange polymer are also fixed together.
8. The preparation method according to claim 7, characterized in that, The substrate is selected from a metal substrate or a silicon dioxide substrate, and the metal substrate is selected from a copper substrate or a nickel substrate; The substrate is a copper substrate with the two-dimensional material film on only one side. Step (3) removes the substrate by wet etching; or... The substrate is a copper substrate with two-dimensional material films on both sides. Step (3) to remove the substrate includes dry etching and wet etching performed sequentially.
Citation Information
Patent Citations
Graphene membrane
CN107847876A
